The Effect of Life Style and Islamic Branding on Consumer Decisions in Buying Muslim Gamis Fashion Products in Bandar Lampung - Winda Anggraini; Heni Noviarita (Universitas Muhammadiyah Jakarta, 2021)
Fashion is considered not only as clothing industry but also shows a person's lifestyle in appearance and becomes part of the identity of a group of people.